2005
DOI: 10.1097/01.ta.0000188129.91271.ab
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time, Contrast-Enhanced Sonography: A New Tool for Detecting Active Bleeding

Abstract: Our retrospective clinical study shows for the first time how US can detect contrast medium extravasation, a significant indicator of active hemorrhage and of need for prompt surgical or interventional treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 23 publications
0
36
0
Order By: Relevance
“…Catalano et al performed CEUS examinations in 83 traumatic emergencies, and their clinical study showed for the fi rst time how US can detect contrast medium extravasation, a signifi cant indicator of active haemorrhage. They concluded that their preliminary work showed that CEUS may be a new tool for detecting active bleeding [13]. However, whether CEUS can evaluate active bleeding from abdominal parenchymal organ trauma is still a matter of debate.…”
Section: Introductionmentioning
confidence: 96%
“…Catalano et al performed CEUS examinations in 83 traumatic emergencies, and their clinical study showed for the fi rst time how US can detect contrast medium extravasation, a signifi cant indicator of active haemorrhage. They concluded that their preliminary work showed that CEUS may be a new tool for detecting active bleeding [13]. However, whether CEUS can evaluate active bleeding from abdominal parenchymal organ trauma is still a matter of debate.…”
Section: Introductionmentioning
confidence: 96%
“…Because the ability to detect the blood flow on CDUS is dependent on the flow velocity, detecting bleeding with a low flow velocity is difficult. Contrast-enhanced ultrasound (CEUS) exhibits 100% sensitivity and 100% specificity for active bleeding and is useful for detecting less dramatic or non-arterial bleeding (13,14). However, no reports have investigated the rate of detection of microbubble flow signals along the needle tract following percutaneous liver biopsy.…”
Section: Introductionmentioning
confidence: 99%
“…2a), and the other was contrast leakage appearing as fountain-like, hyperechoic jet (Fig. 2b) [8]. After treatment, CEUS demonstrated that active bleeding disappeared.…”
Section: Resultsmentioning
confidence: 96%